The Effectiveness of Granting Funding at Foundation School / Raudhatul Athfal Bina Kreatif Institution in Batang Kuis District, Deli Serdang Regency - Rosida Sitorus; Heri Kusmanto; Isnaini Isnaini (Budapest International Research and Critics University, 2021)
This study aims to evaluation the Effectiveness of Granting Funding at Foundation School / Raudhatul Athfal Bina Kreatif Institutions in Batang Kuis District, Deli Serdang Regency. This study uses the Research Instruments In qualitative research, the main instrument is the researcher himself, but the research instrument that the researcher uses to complement the data and compare it with the data that has been found through observation guidelines, interview guidelines, study and review of documents related to the object of research. Sources of data used in this study are divided into two sources, namely primary data sources and secondary data sources. The results of this study indicate that 1.The benefits of providing grant funds for schools at RA Bina Kreatif Educational Institutions/Foundations in Batang Kuis District, Deli Serdang Regency. 2.There were obstacles in the use of grant funds by RA Bina Kreatif schools in providing grants to schools. 3.The Head of Raudhatul Athfal Bina Kreatif has submitted an Accountability Report Number: 075 / RA-BK / SEK / V / 2019. Date, May 20, 2019, regarding the submission of the 2019 APBD-SU Financial Accountability Report.